2019
DOI: 10.1111/resp.13518
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the benefits following pulmonary rehabilitation: Achievable or not?

Abstract: Pulmonary rehabilitation (PR) improves exercise capacity, health-related quality of life (HRQoL) and dyspnoea in patients with COPD and other lung conditions. Once PR is completed, the benefits gained begin to decline unless patients continue to exercise regularly. Due to limited evidence in other lung conditions, this review aims to examine the current evidence regarding maintenance exercise programmes for patients with COPD and to determine the types of programmes that are able to maintain the benefits gaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
63
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 41 publications
0
63
0
Order By: Relevance
“…Long-term follow-up following PR is often poorly documented, with an average of less than 50% of participants evaluated 1 year after the PR. 47 In the present study, more than two thirds of the participants were evaluated at 1 year, regardless of the age, suggesting that older age does not specifically impact PR attendance. Eight weeks of home-based intervention follows by one visit 6 months after (M8), seems to facilitate the adherence and maintaining PR benefits up to 1 year after the programme.…”
mentioning
confidence: 50%
“…Long-term follow-up following PR is often poorly documented, with an average of less than 50% of participants evaluated 1 year after the PR. 47 In the present study, more than two thirds of the participants were evaluated at 1 year, regardless of the age, suggesting that older age does not specifically impact PR attendance. Eight weeks of home-based intervention follows by one visit 6 months after (M8), seems to facilitate the adherence and maintaining PR benefits up to 1 year after the programme.…”
mentioning
confidence: 50%
“…A meta-analysis of five trials of 445 participants with COPD showed that individuals allocated to a supervised maintenance exercise programme experienced fewer respiratory-cause admissions (risk ratio 0.62; CI 0.47 to 0.81; p<0.001)7 compared with those receiving usual care; however, this finding was heavily influenced by one trial8 that provided the longest programme duration (3 years) of supervised maintenance. The optimal strategy for maintaining the initial benefits from pulmonary rehabilitation remains unclear with the authors of the Australia and New Zealand Pulmonary Rehabilitation Clinical Practice Guidelines calling for further research and economic evaluation of a weekly supervised maintenance programme 4 9. An economic evaluation of a single 2-hour maintenance pulmonary rehabilitation session at 3, 6 and 9 months after the initial programme has shown it to be cost-effective 10.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated the effects of ongoing support after PR on the maintenance of benefits and are included in a recent review paper. 11 Most studies used a combination of interventions including pedometers, phone calls and/or supervised exercise at a reduced frequency than in the initial PR programme. A systematic review with meta-analyses 12 demonstrated a significant reduction in the risk of experiencing at least one hospital admission for a respiratory cause in those receiving a supervised maintenance exercise programme compared to usual care (risk ratio: 0.62 (95% CI: 0.47-0.81), n = 278).…”
mentioning
confidence: 99%